1992
DOI: 10.1007/bf00636219
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of the phagocytic function in guinea pig peritoneal macrophages by physical activity stress

Abstract: A study was made of all the different stages of the phagocytic function in peritoneal macrophages from male guinea pigs [3 (SD 1) months old] before, immediately after, and 24 h after being subjected to stress from physical activity (swimming until exhaustion). The early (10 min) and late (40 min) adherence to tissue substrates, chemotaxis, attachment and phagocytosis of Candida albicans, ingestion of inert particles (latex beads), and basal oxidative metabolism [measured by nitroblue tetrazolium (NBT) reducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 21 publications
5
23
0
Order By: Relevance
“…Other results also support this idea with respect to chemotaxis. For example it has been observed that, after swimming until exhaustion, guinea-pig peritoneal macrophages showed an increased chemotactic capacity with a concomitant increase in plasma corticosterone concentration (Ortega et al 1992). In the present experiments, 0-72 ,smol 1I1 of corticosterone not only stimulated macrophage chemotaxis but also acted as a chemoattractant for these cells (see Fig.…”
Section: Discussionsupporting
confidence: 51%
“…Other results also support this idea with respect to chemotaxis. For example it has been observed that, after swimming until exhaustion, guinea-pig peritoneal macrophages showed an increased chemotactic capacity with a concomitant increase in plasma corticosterone concentration (Ortega et al 1992). In the present experiments, 0-72 ,smol 1I1 of corticosterone not only stimulated macrophage chemotaxis but also acted as a chemoattractant for these cells (see Fig.…”
Section: Discussionsupporting
confidence: 51%
“…Stress from noise can reduce release of superoxide ion and interleukin-1 from macrophages, whereas stress imposed by restraint or opioid dependency can produce reduction of "phagocytic activity (24)(25)(26). On the other hand, the stress of physical activity can actually enhance certain macrophage functions such as cytostatic activity, chemotaxis and phagocytosis (27,28). The potential mediator loop or loops that control these effects remain to be established.…”
Section: Molecular Biology Of Macrophage Activationmentioning
confidence: 96%
“…Particle ingestion: Evaluated by the counts of the number of neutrophils ingesting at least one particle of latex and the number of particles inside 100 neutrophils after incubation at 37ºC on Kartell plates for 30 min of 200 µl of the dilution of the neutrophils in Hank liquid and the addition and re-incubation of 20 µl of latex to 1% in Hank, and the fixation and staining of plates (De La Fuente 1985;Ortega et al 1992). technique (1985), measuring by spectrophotometry at 525 nm of λ the reduction of nitroblue of tetrazolium to formazan by oxygenated compounds liberated by the neutrophil in samples stimulated by phagocytosis with latex particles (stimulated digestion) compared to others in which only Hank liquid (unstimulated digestion) had been added.…”
Section: Immunology Testsmentioning
confidence: 99%